Urban (in) formality and the new unsustainable landscape of the Global South: Case study of megacity Dhaka - Swapan, Mohammad SH; Zaman, Atiq; Lehmann, Steffen (Routledge, 2020)
How urban informality, public space, growth and inequality are interconnected has long been a field of scholarly reflection and research. The term ‘informality’ becomes synonymous to the urbanisation process, practice and outcome in the Global South. The concept has been preluded with neoliberal economics and governance thinking. Informality has prevailed as a dominant characteristic of urbanisation of poverty and as a form of shelter. However, the discourse of urban informality in the Global South has undergone critical transformation in recent scholarship - it is no longer synonymous to poverty or ‘subaltern urbanism’ but rather associated with various forms of entrepreneurship, wealth, exchange and power. Planning is not solely performed by planners and architects, but also by other critical stakeholders including developers, builders, civil societies and privileged residents who sometimes render and obscure what is considered as ‘formal’ or ‘legal’. Thus, a new discourse is evolving in the literature that characterises this emerging landscape of urban informality; popularly termed as ‘elite informality’ or ‘entitled urbanism’. This chapter aims to critically analyse such transformation within the context of megacities in the Global South using a systematic and comparative literature review amongst various parts of the world. The chapter also presents the effects of elite informality on sustainable urbanisation in megacity Dhaka (Bangladesh) by exploring the contested spaces along the urban periphery in order to better understand the increasing involvement of power and politics in shaping the entire planning regime. Finally, the chapter reflects on the role of local and small-scale projects to better understand the transitional and manipulated governance practice to ensure sustainable urbanisation in the Global South.